Do Genes Play a Role in the Decoy Effect? - Zeng, Jianmin; Zhao, Xinyi; Qin, Huihui; Hou, Xingrong; Zhang, Qinglin (Frontiers in Psychology, 2020)
The decoy effect arises when the ratio of choosing B from A and B options is lower than the ratio of choosing B from A, B and D options, wherein D is dominated by B. This decision pattern is obviously unreasonable but quite common. Previous research suggested that impulsive people have stronger decoy effect. Rs806379, as a single-nucleotide-polymorphism (SNP) locus of cannabis receptor 1 gene (CNR1), has significant effect on impulsivity – people of A/A genotype are more impulsive than others. Therefore, rs806379 may relate to the decoy effect, which was tested in this study. Participants (359 Han Chinese college students) finished a task of the decoy effect, in which they made decisions between two or three mobile hard disks with various prices, and provided saliva for genotyping. The results revealed the existence of the decoy effect. Furthermore, we found that participants with A/A genotype (251 Han Chinese college students) showed stronger decoy effect than others, when the prices were not high. This is the first attempt to study the decoy effect from a gene perspective. The result shows that even an SNP of a gene can have a significant association with complex human economic decision-making activities.